Maillard reaction products formation and antioxidative power of spray dried camel milk powders increases with the inlet temperature of drying. (May 2021) - Perusko, Marija; Ghnimi, Sami; Simovic, Ana; Stevanovic, Nikola; Radomirovic, Mirjana; Gharsallaoui, Adem; Smiljanic, Katarina; Van Haute, Sam; Stanic-Vucinic, Dragana; Cirkovic Velickovic, Tanja
Abstract: Demand for camel milk (CM) is increasing worldwide, due to its high nutritious value and health benefits. In this study, whole CM powders were produced by spray drying (SD) at six inlet temperatures (190 °C–250 °C) and by freeze drying (FD). Physicochemical and functional properties of CM powder proteins were investigated. SD at higher inlet temperatures (230 °C–250 °C) resulted in higher extent of Maillard reaction (MR), in comparison to lower temperatures (190 °C–200 °C) and FD treatment. Both treatments had negative effect on casein solubility, while whey proteins remained soluble and slightly increased its solubility with the extent of MR. The CM powders obtained at higher inlet temperatures demonstrated improved antioxidant activity. Secondary structure of whey proteins did not differ among the samples, while surface hydrophobicity of whey proteins was higher in all SD than in FD samples, suggesting only limited denaturation of camel whey proteins at higher inlet temperatures of drying. Thus, the effects of SD under the conditions applied in our study did not decrease camel whey protein solubility, while drying procedure itself regardless of temperature decreased solubility of camel milk caseins. MR generated during CM processing could be an important means of compensating for the lack of antioxidant protection normally associated with β-lactoglobulin but happens to be absent from this milk. Highlights: Camel milk powders were prepared by spray drying at six air inlet temperatures. Caseins demonstrated poor solubility, while whey proteins remained soluble. Higher inlet temperatures resulted only in limited denaturation of whey proteins. Antioxidant power positively correlated with the extent of MR. MR may provide antioxidant protection given the milk's lack of β-lactoglobulin.